Seasonal Variations in Toxic Metal Levels of Two Fish Species, Mugil cephalus and Mullus barbatus and Estimation of Risk for Children - Yaman, Mehmet; Karaaslan, Nagihan M.; Yaman, Ibrahim H. (Springer, 2014)
Concentrations of five toxic metals were determined in two fish species namely, Mugil cephalus and Mullus barbatus consumed in two neighboring Turkish cities during 2010-2011. Lead concentrations (mean 900 mu g kg(-1)) for M. cephalus were found to be higher than the maximum allowances concentration (MAC) of 300 mu g kg(-1). Similarly, Cr (mean 410 mu g kg(-1)), Ni (mean 331 mu g kg(-1)) and Cu (mean 834 mu g kg(-1)) concentrations in M. cephalus were significantly higher than in M. barbatus (mean 341 mu g Cr kg(-1), 256 mu g Ni kg(-1) and 568 mu g Cu kg(-1)). Although concentrations of some metals exceed the limits set by the authorities, the estimated non-carcinogenic and carcinogenic health risks by the Target Hazard Quotient and target carcinogenic risk indicate that there is no carcinogenic risk for humans, and the risk of developing cancer over a human lifetime is between 2 and 12 in 1,000,000.
Keywords: Toxic metals; Fish; Atomic absorption; ICP-AES; Risk assessment; STAT